Five-year results from the prospective European multicentre cohort study on radiofrequency segmental thermal ablation for incompetent great saphenous veins - Thomas M. Proebstle; Bernt Alm; Oliver Göckeritz; Christian Wenzel; T. Noppeney; C Lebard; Carmine Sessa; D. Creton; O. Pichot (2015)
This was a prospective study of radiofrequency segmental thermal ablation (RFA) for the treatment of incompetent varicose great saphenous veins (GSVs). The present report describes long-term follow-up at 5 years.The 5-year follow-up of this multicentre European study included assessment of the Venous Clinical Severity Score (VCSS), and GSV occlusion and reflux on duplex imaging.A total of 225 patients had 295 GSVs treated by RFA, achieving an initial vein occlusion rate of 100 per cent. With 80·0 per cent compliance, Kaplan-Meier analyses showed a GSV occlusion rate of 91·9 per cent and a reflux-free rate of 94·9 per cent at 5 years. Among the 15 GSVs noted with reflux during follow-up, only three showed full recanalization of the GSV at 1 week, 6 months and 3 years. Of the 12 legs with partial recanalization, reflux originated at the saphenofemoral junction in ten, with a mean length of the patent segment of 5·8 (range 3·2-10) cm; only six patients were symptomatic. Mean(s.d.) VCSS scores improved from 3·9(2·1) at baseline to 0·6(1·2), 0·9(1·3) and 1·3(1·7) at 1, 3 and 5 years.At 5 years RFA proved to be an efficient endovenous treatment for incompetent GSVs in terms of sustained clinical and anatomical success for the vast majority of treated patients.